2021
DOI: 10.3389/fneur.2021.801499
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Common Dizziness Associated Symptoms on Dizziness Handicap in Older Adults

Abstract: Background: A cross-sectional observational study was designed to determine the impact of dizziness associated symptoms on the dizziness handicap inventory (DHI) in older adults (≥60 years).Methods: In total, 785 individuals referred to a multidisciplinary dizziness unit were assessed. Participants completed self-report questionnaires with general questions about symptoms of dizziness as well as the DHI. The DHI subscores (physical, functional, emotional) were calculated. Medical diagnoses were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Tino. P et al, 2017) found similar results in a review on 'the Impact of Common Dizziness Associated Symptoms on Dizziness Handicap in Older Adults where most patients reported swaying dizziness (60.6%) [28]. Jan Löhler et al (2019) said that hearing impairment was associated with ageing and was becoming more common in a review on detection, treatment, and associated risks of hearing impairment in old age [29].…”
Section: Discussionmentioning
confidence: 84%
“…Tino. P et al, 2017) found similar results in a review on 'the Impact of Common Dizziness Associated Symptoms on Dizziness Handicap in Older Adults where most patients reported swaying dizziness (60.6%) [28]. Jan Löhler et al (2019) said that hearing impairment was associated with ageing and was becoming more common in a review on detection, treatment, and associated risks of hearing impairment in old age [29].…”
Section: Discussionmentioning
confidence: 84%
“…Several studies showed that dizziness is associated with multiple neurosensory deficits (9), including various hearing problems (8), hearing loss, hearing impairment (7), ear pressure (7), tinnitus (8), and impaired vision (15). Moreover, associations between dizziness and functional disability (17,18), loss of autonomy and decreased chances for independent living (19), impaired mobility (7), impaired balance (7), gait disturbance (20), and falls (7, 21) were found. There is a lack of studies, in particular in low resourced countries, investigating associations between dizziness and a wide range of mental and physical health outcomes.…”
Section: Pengpid and Peltzermentioning
confidence: 99%
“…Older adults with dizziness often suffer from multisensory deficits, such as central vertigo bilateral vestibulopathy, and benign paroxysmal positional vertigo ( 8 , 9 ). Especially in older individuals, vertigo and dizziness contribute to physical inactivity ( 10 ), social isolation, depression ( 11 ), dizziness-associated disabilities ( 12 ), and a higher risk of falls ( 13 , 14 ). Therefore, dizziness and vertigo per-se and commonly associated psychiatric comorbidities, such as anxiety or depression, can cause increased healthcare utilization ( 15 ), incurring a high economic burden ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%